Paxillin: a new vinculin-binding protein present in focal adhesions (The Rockefeller University Press, 1990)
The 68-kD protein (paxillin) is a cytoskeletal component that localizes to the focal adhesions at the ends of actin stress fibers in chicken embryo fibroblasts. It is also present in the focal adhesions of Madin- Darby bovine kidney (MDBK) epithelial cells but is absent, like talin, from the cell-cell adherens junctions of these cells. Paxillin purified from chicken gizzard smooth muscle migrates as a diffuse band on SDS- PAGE gels with a molecular mass of 65-70 kD. It is a protein of multiple isoforms with pIs ranging from 6.31 to 6.85. Using purified paxillin, we have demonstrated a specific interaction in vitro with another focal adhesion protein, vinculin. Cleavage of vinculin with Staphylococcus aureus V8 protease results in the generation of two fragments of approximately 85 and 27 kD. Unlike talin, which binds to the large vinculin fragment, paxillin was found to bind to the small vinculin fragment, which represents the rod domain of the molecule. Together with the previous observation that paxillin is a major substrate of pp60src in Rous sarcoma virus-transformed cells (Glenney, J. R., and L. Zokas. 1989. J. Cell Biol. 108:2401-2408), this interaction with vinculin suggests paxillin may be a key component in the control of focal adhesion organization.